Readers and Their Fictions in the Novels and Novellas of Gottfried Keller - Hart, Gail K. (UNC Studies in the Germanic Languages and Literatures, 1989)
This study seeks to alter our understanding of Keller's realism by problematizing the act of reading within fiction. The story of reading in Keller's fiction is a self-conscious meditation on the schism between life and its literary representation-and it emphasizes the incapacity of that representation to actually and substantially influence the life it is based on. This has consequences for the didactic writer. The act of reading here generally involves a collision between fiction and its other and a move (or tragic failure to move) toward an acceptance and affirmation of the non-correspondence between life and literature, a process that renders moral didacticism a quixotic project. This position runs counter to the prevailing view of Keller as a consciously didactic author who tried to create a credible copy of reality in order to revise and repair the real world by inspiring readers to make the depicted improvements in their nonfictional universe.